Tribhuvan Vishwovidhyalaya Pathyakram Vikash Kendra ra Star Nirdharan: Uchhashikshyako Bikaral Chunauti - Sharma, Nilkumar (Tribhuvan University Journal, 2010)
Not available. Key words: Curriculam; Tribhuvan University; Higher Education Tribhuvan University Journal Vol. XIX, 1996 Page: 165-172 Uploaded Date: 24 Nov., 2010